False memories in forensic psychology: do cognition and brain activity tell the same story? - Pérez-Mata, Nieves; Diges, Margarita (Frontiers in Psychology, 2024)
One of the most important problems in forensic psychology is the impossibility of reliably discriminating between true and false memories when the only prosecution evidence comes from the memory of a witness or a victim. Unfortunately, both children and adults can be persuaded that they have been victims of past criminal acts, usually of a sexual nature. In adults, suggestion often occurs in the context of suggestive therapies based on the belief that traumatic events are repressed, while children come to believe and report events that never occurred as a result of repeated suggestive questioning. Cognitive Researchers have designed false memory paradigms (i.e., misinformation effect, Deese-Roediger-McDermott paradigm, event implantation paradigm) to first form false memories and then determine whether it is possible to reliably differentiate between false and true memories. In the present study, we review the contribution of cognitive research to the formation of false memories and the neuropsychological approaches aimed to discriminate between true and false memories. Based on these results, we analyze the applicability of the cognitive and neuropsychological evidence to the forensic setting.